Treatment Services in the Juvenile Justice System: Examining the Use and Funding of Services by Youth on Probation - Uding, Clair (Youth violence and juvenile justice, 2019)
Youth enter the juvenile justice system with a variety of service needs, particularly for mental health problems. Research has examined the extent to which youth have mental health disorders, primarily among detained youth, and factors associated with treatment referrals, but little research has examined youth on probation and the actual use of services. Using data obtained from the Maricopa County Juvenile Probation Department from July 2012 through August 2014 (N = 3,779), the current study examines (1) the factors associated with receiving treatment services while on probation and (2) the factors associated with receiving treatment services through different funding streams. Findings reveal that only about 25% of the sample of youth on probation received treatment services, suggesting the underservicing of youth. Consistent with prior research, there were also racial and ethnic disparities concerning treatment use, with Blacks and Latinos less likely to receive services. Additionally, certain characteristics of youth and their background influenced the funding source for treatment services. Implications for policy and research are discussed in light of these findings.